A Systematic Review of Augmented Reality Applications in Language Learning - Majid, Siti Norzaimalina Abd; Salam, Abdul Rahim (International Journal of Emerging Technologies in Learning (iJET), 2021)
Augmented reality (AR) is one of the emerging technologies gradually venturing into the education field. Although AR is strongly linked to subjects related to Science, Mathematics, and Technology in schools and tertiary education, there is no mention of AR in non-technical subjects, such as language. Thus, this study aims to discover the AR application trends in language learning and the language skills prevalent in AR usage. In this systematic literature review, AR-related research in language learning began in 2016 and has continued to be on the rise. Furthermore, the preferred language skills used with AR technology required lower cognitive levels, such as identifying words, understanding meanings, and spelling, and pronouncing words. Based on the gap indicating the rare usage of AR for more complex and critical language skills, such as reading and writing, this study hopes to enlighten the researchers, educators, and application developers to focus on developing AR applications for languages other than English, incorporate higher-order learning outcomes in the language learning activities, and pursue qualitative investigations.